BIOAVAILABILITY STUDY OF PHYSICAL MIXTURE OF CARBAMAZEPINE AND AMINO ACIDS - Dewi Isadiartuti; Budiati, Tutuk; Martodihardjo, Suwaldi (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: This study aimed to evaluate the bioavailability of physical mixture (PM) of carbamazepine (CBZ) and amino acids (glycine, alanine, and lysine), includes a parameter tmax, Cmax and AUC0-12. Methods: PM made by weighing CBZ with amino acids (glycine, alanine, and lysine) equimolar and mix both components with a mortar until a homogeneous mixture. PM obtained was characterized using differential thermal analysis (DTA), Fourier transform infrared (FTIR) and optical microscopy. Bioavailability was conducted after obtaining ethical clearance from Faculty of Veterinary Airlangga University to five New Zealand Rabbits for each treatment. CBZ levels in blood plasma were determined by HPLC analysis method. Results: The results of the DTA thermogram and infrared spectra showed that CBZ compound mixed with the components of the constituent amino acids. Time achieve maximum levels value (tmax) PM of CBZ-GLY, CBZ-ALA, and CBZ-LYS, respectively, for 5.09, 3.85, and 3.93 hours faster than the tmax value of CBZ at 6.14 hours. Cmax value of PM CBZ-LYS at 4.85 mg/mL higher than CBZ at 2.56 mg/mL and AUC0-12 value PM CBZ-LYS at 37.31 hrs ug/mL greater than CBZ at 20.59 Î¼g hrs/mL. Conclusion: From the research can be concluded that PM able to improve the bioavailability of CBZ. The value tmax of PM CBZ-amino acids (GLY, ALA, and LYS) faster than CBZ. PM of CBZ-LYS provides Cmax and AUC0-12 value greater than CBZ compounds. Keywords: Carbamazepine, Glycine, Alanine, Lysine, Physical mixture, Bioavailability.